THE ASSOCIATION OF CIRCULATING SCLEROSTIN LEVEL WITH MARKERS OF BONE METABOLISM IN PATIENTS WITH THYROID DYSFUNCTION - Mihaljević, Olgica B.; Živančević-Simonović, Snežana; Lučić-Tomić, Aleksandra; Živković, Irena; Minić, Rajna; Mijatović-Todotović, Ljiljana; Jovanović, Zorica; Anđelković, Marija; Stanojević-Pirković, Marijana (Journal of Medical Biochemistry, 2020)
Background: The aim of this study was to compare serum sclerostin concentrations in patients with thyroid dysfunction with euthyroid control subjects and to assess the relationship between sclerostin and markers of bone metabolism (osteocalcin and beta-cross-laps). Methods: The study included 30 patients with thyroid dysfunction (hypothyroidism, hyperthyroidism and subclinical hyperthyroidism) and ten euthyroid controls. Free thyroxine (FT4) was measured by radioimmunoassay, while thyroid stimulating hormone (TSH) concentration was determined immunoradiometrically. We used an ELISA kit to determine the sclerostin level. The electrochemiluminescence method was applied for measuring the bone markers. Results: Sclerostin levels were significantly lower in hypothyroid patients (p=0.009) and significantly elevated in hyperthyroid patients (p=0.008) compared to control values. Hyperthyroid patients also had higher sclerostin than patients with subclinical hyperthyroidism (p=0.013). Sclerostin concentrations were negatively correlated with TSH levels (r=-0.746, p<0.001), but positively with FT4 (r=0.696, p < 0.001). Moreover, sclerostin was positively associated with osteocalcin (r=0.605, p=0.005) and beta-cross-laps levels (r=0.573, p=0.008) in all thyroid patients. Conclusions: Serum sclerostin is significantly affected in subjects with thyroid dysfunction. Both sclerostin and thyroid status affect bone homeostasis, which is reflected through the significant correlations with osteocalcin and beta-cross-laps. Keywords: beta-cross-laps, bone metabolism, osteocalcin, sclerostin, thyroid dysfunction